2020
DOI: 10.1016/j.buildenv.2020.106673
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interunit dispersion in 2D street canyons: A scaled outdoor experiment

Abstract: A B S T R A C TInterunit dispersion problems have been studied previously mainly through on-site measurements, wind tunnel tests, and CFD simulations. In this study, a scaled outdoor experiment was conducted to examine the interunit dispersion characteristics in consecutive two-dimensional street canyons. Tracer gas (CO 2 ) was continuously released to simulate the pollutant dispersion routes between the rooms in street canyons. The wind velocity, wind direction, air temperature, and tracer gas concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Nevertheless, the cascading effect found in this work is an often-overlooked pathway of exposure. This effect was also found by many other previous research, both with numerical simulations [21,22] and scaled outdoor observations [29]. Furthermore, with cross ventilation, the flow from outdoor to indoor and the flow passing through the whole building could be another exposure pathway between different rooms or even different buildings, as concluded by [20].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, the cascading effect found in this work is an often-overlooked pathway of exposure. This effect was also found by many other previous research, both with numerical simulations [21,22] and scaled outdoor observations [29]. Furthermore, with cross ventilation, the flow from outdoor to indoor and the flow passing through the whole building could be another exposure pathway between different rooms or even different buildings, as concluded by [20].…”
Section: Discussionsupporting
confidence: 80%
“…The parameter air change per hour (ACH) is applied to evaluate the effect of the natural ventilation in the room [29]. Equations ( 3) and ( 4) are the definition of ACH.…”
Section: Definition Of Critical Parameters For Ventilation and Exposure Assessment 221 Air Change Per Hour (Ach)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ai et al [10] used CFD simulation to study inter-unit dispersion characteristics of indoor pollutants in multi-story single-sided natural ventilated buildings and analyzed the effects of wind direction and balconies. Recently, Dai et al [11] adopted outdoor scale experiment to explore the contaminant transmission route of natural ventilation buildings in the street canyon.…”
Section: Introductionmentioning
confidence: 99%
“…Street canyons also play a significant role in interunit dispersion. A study found the CO2 tracer gas being main transported in the vortex direction formed by the freestream inside the canyon ( Dai, Mak, Zhang, Cui, & Hang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%